LUBANG BIOPORI CACING TANAH DAN DAMPAKNYA TERHADAP RESAPAN AIR TANAH - Eladisa Ganjari, Leo (Widya Warta, 2009)
Any work, which is in nature both   ossifying and closing   ground surface,   causes the decline  of  ground  water infiltration.  Some  efforts  to  enlarge  ground  water  infiltration  have already  been done,  for example,  by  making  infiltration wells and  bioporic  infiltration holes. Earthworms naturally do some activities which contribute to make ground water infiltrate. Due to this fact, a research needs conducting on bioporic infiltration holes of earthworms. This research was performed in Sukoharjo, Surakarta from September 2007 up to July 2008. The study aimed to search the diameter and amount of width units of bioporic infiltration holes of earthworms. The number of infiltration holes of earthworms was counted on the basis of measurement plots of 50 cm x 50 cm. The plots, 20 in number, were placed on a piece of land randomly. Each hole of earthworms (biopore) in every plot was measured to find its diameter. The result of the research showed that the average diameter of bioporic  infiltration holes of earthworms was 4,58 mm, and there were 20 holes found in every square meter of land. The bioporic infiltration holes of earthworm could extend the infiltration area of ground water as many as 873 times.